Characterization of the Early Events in Dengue Virus Cell Entry by Biochemical Assays and Single-Virus Tracking - van der Schaar, Hilde M. (American Society for Microbiology (ASM), 2007)
In this study, we investigated the cell entry characteristics of dengue virus (DENV) type 2 strain S1 on mosquito, BHK-15, and BS-C-1 cells. The concentration of virus particles measured by biochemical assays was found to be substantially higher than the number of infectious particles determined by infectivity assays, leading to an infectious unit-to-particle ratio of approximately 1:2,600 to 1:72,000, depending on the specific assays used. In order to explain this high ratio, we investigated the receptor binding and membrane fusion characteristics of single DENV particles in living cells using real-time fluorescence microscopy. For this purpose, DENV was labeled with the lipophilic fluorescent probe DiD (1,1′-dioctadecyl-3,3,3′,3′-tetramethylindodicarbocyanine, 4-chlorobenzenesulfonate salt). The surface density of the DiD dye in the viral membrane was sufficiently high to largely quench the fluorescence intensity but still allowed clear detection of single virus particles. Fusion of the viral membrane with the cell membrane was evident as fluorescence dequenching. It was observed that DENV binds very inefficiently to the cells used, explaining at least in part the high infectious unit-to-particle ratio. The particles that did bind to the cells showed different types of transport behavior leading to membrane fusion in both the periphery and perinuclear regions of the cell. Membrane fusion was observed in 1 out of 6 bound virus particles, indicating that a substantial fraction of the virus has the capacity to fuse. DiD dequenching was completely inhibited by ammonium chloride, demonstrating that fusion occurs exclusively from within acidic endosomes.